Time Synchronization Technique Hardware Implementation for OFDM Systems With Hermitian Symmetry for VLC Applications - Lozada D. Randy; Betancourt P. Juan Sebastian; San Millan H. Enrique (IEEE Access, 2023)
The main contribution of this work is the proposal and hardware implementation of an algorithm for the time synchronization of orthogonal frequency division multiplexing (OFDM) modulation with Hermitian symmetry for visible light communications (VLC) systems, using only the real component of the transmitted signal. OFDM systems with Hermitian Symmetry are able to satisfy the high data rates demanded by many VLC systems, as well as deal with inter-symbol interference (ISI). However, these systems are characterized by being very vulnerable to synchronization problems in both time and frequency. Time synchronization being the most critical. In this paper, a novel time synchronization technique for OFDM systems with Hermitian Symmetry is proposed. This technique is based on the inclusion of a post-FFT synchronization stage to achieve time synchronization with one-sample precision. For this purpose, the relationship that exists between an offset in the frequency domain with an offset in the time domain is used, and with this information the correction of the frequency offset from the time domain is performed. An original and novel algorithm has been designed and implemented in hardware, which uses the cyclic prefix (CP) elimination stage to perform the time correction. The performance validation of the proposed technique is done with the implementation, using the ZYBO $^{{^{ TM}}}$ development board, of a complete OFDM system applied to a real VLC system.